Lipid Paradox in Statin-Naïve Acute Ischemic Stroke But Not Hemorrhagic Stroke - Cheng, Kai-Hung; Lin, Jr-Rung; Anderson, Craig S.; Lai, Wen-Ter; Lee, Tsong-Hai, the SRICHS Group; Lee, Tsong-Hai; Chang, Yeu-Jhy; Chang, Chien-Hung; Wu, Hsiu-Chuan; Huang, Kuo-Lun; Chang, Ting-Yu; et al. (Frontiers in Neurology, 2018)
Background– Low lipid level is associated with better cardiovascular outcome. However, lipid paradox indicating low lipid level has worse outcome can be seen under acute injury in some diseases. The present study was designed to clarify the prognostic significance of acute-phase lipid levels within 1 day after admission for stroke on mortality in first-ever, statin-naïve acute ischemic (IS) and hemorrhagic stroke (HS). Methods– This observational study was conducted using the data from Stroke Registry In Chang-Gung Healthcare System (SRICHS) between 2009 and 2012. Patients with recurrent stroke, onset of symptoms >1 day and history of lipid-lowering agents prior to index stroke were excluded. Stroke was classified into IS and hypertension-related HS. The primary outcomes were 30-day and 1-year mortality identified by linkage to national death registry for date and cause of death. Receiver operating characteristic curve analysis and multivariate Cox proportional hazard models were used to examine the association of admission lipids with mortality. Results– Among 18,268 admitted stroke patients, 3,746 IS and 465 HS were eligible for analysis. In IS, total cholesterol (TC) <163.5mg/dL, triglyceride (TG) <94.5mg/dL, low-density lipoprotein (LDL) <100mg/dL, non-high-density lipoprotein cholesterol (non-HDL-C) <130.5mg/dL and TC/HDL ratio <4.06 had significantly higher risk for 30-day/1-year mortality with hazard ratio (HR) of 2.05/1.37, 1.65/1.31, 1.68/1.38, 1.80/1.41 and 1.58/1.38, respectively, compared to high TC, TG, LDL, non-HDL-C and TC/HDL ratio (all p<0.01). In HS, lipid profiles were not associated with mortality, except HDL for 30-day mortality (p=0.025) and high uric acid concentrations for 30-day and 1-year mortality (p=0.002, 0.012, respectively). High fasting glucose and high NIHSS score at admission were associated with higher 30-day and 1-year mortality in both IS and HS and low blood pressure only in IS (p<0.05). Synergic effects on mortality were found when low lipids were incorporating with high fasting glucose, low blood pressure and high NIHSS score in IS (p<0.05). Conclusions- Lipid paradox showing low acute-phase lipid levels with high mortality could be seen in statin-naïve acute IS but not HS. The mortality in IS was increased when low lipids were incorporating with high fasting glucose, low blood pressure and high NIHSS score.